Double-zigzag boron chain-enhanced Vickers hardness and manganese bilayers-induced high d-electron mobility in Mn3B4. Issue 5 (21st January 2019) - Ma, Shuailing; Bao, Kuo; Tao, Qiang; Xu, Chunhong; Feng, Xiaokang; Zhao, Xingbin; Ge, Yufei; Zhu, Pinwen; Cui, Tian
Abstract : The D7b -type structure Mn3 B4 was fabricated by high-temperature and high-pressure (HPHT) methods. Abstract : The D7b -type structure Mn3 B4 was fabricated by high-temperature and high-pressure (HPHT) methods. Hardness examination yielded an asymptotic Vickers hardness of 16.3 GPa, which is much higher than that of Mn2 B and MnB2 . First principle calculations and XPS results demonstrated that double zigzag boron chains form a strong covalent skeletons, which enhances this structure's integrity with high hardness. Considering that the hardensses of MnB and Mn3 B4 are higher than those of Mn2 B and MnB2, zigzag and double zigzag boron backbones are superior to isolated boron and graphite-like boron layer backbones for achieving higher hardness. This situation also states that a higher boron content is not the sole factor for the higher hardness in the low boron content transition metal borides. Futhermore, the co-presence of metallic manganese bilayers contribute to the high d-electron mobility and generate electrical conductivity and antiferromagnetism in Mn3 B4 which provide us with a new structure prototype to design general-purpose high hardness materials.